TO THE FORMATION OF PEDAGOGICAL CULTURE OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the professional-pedagogical of the teacher and degree of their importance for students in formation of their pedagogical culture are considered.
Keywords: pedagogical culture; morality; spirituality